A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

Extreme mismatch between phytoplankton and grazers during Arctic spring blooms and consequences for the pelagic food-web - Paul E. Renaud; Malin Daase; Eva Leu; Maxime Geoffroy; Sünnje Basedow; Mark Inall; Karley Campbell; Emilia Trudnowska; Einat Sandbank; Frida Cnossen; Muriel Dunn; Lionel Camus; et al. (Progress in Oceanography, 2024)

Dependency of simulated tropical Atlantic current variability on the wind forcing - Kristin Burmeister; Franziska U. Schwarzkopf; Willi Rath; Arne Biastoch; Peter Brandt; Joke F. Lübbecke; Mark Inall (Ocean Science, 2024)
The upper wind-driven circulation in the tropical Atlantic Ocean plays a key role in the basin-wide distribution of water mass properties and affects the transport of heat, freshwater, and biogeochemical tracers such as oxygen or nutrients. It is crucial to improve our understanding of its long-term behaviour, which largely relies on model simulations and applied forcing due to sparse observational data coverage, especially before the mid-2000s. Here, we apply two different forcing products, the Coordinated Ocean-ice Reference Experiments (CORE) v2 and the Japanese 55-year Reanalysis (JRA55-do) surface dataset, to a high-resolution ocean model. Where possible, we compare the simulated results to long-term observations. We find large discrepancies between the two simulations regarding the wind and current field. In the CORE simulation, strong, large-scale wind stress curl amplitudes above the upwelling regions of the eastern tropical North Atlantic seem to cause an overestimation of the mean and seasonal variability in the eastward subsurface current just north of the Equator. The wind stress curl of JRA55-do forcing shows much finer structures, and the JRA55-do simulation is in better agreement with the mean and intraseasonal fluctuations in the subsurface current found in observations. The northern branch of the South Equatorial Current flows westward at the surface just north of the Equator. On interannual to decadal timescales, it shows a high correlation of R=0.9 with the zonal wind stress in the CORE simulation but only a weak correlation of R=0.35 in the JRA55-do simulation. We also identify similarities between the two simulations. The strength of the eastward-flowing North Equatorial Counter Current located between 3 and 10° N covaries with the strength of the meridional wind stress just north of the Equator on interannual to decadal timescales in the two simulations. Both simulations present a comparable mean, seasonal cycle and trend of the eastward off-equatorial subsurface current south of the Equator but underestimate the current strength by half compared to observations. In both simulations, the eastward-flowing Equatorial Undercurrent weakened between 1990 and 2009. In the JRA simulation, which covers the modern period of observations, the Equatorial Undercurrent strengthened again between 2008 to 2018, which agrees with observations, although the simulation underestimates the strengthening by over a third. We propose that long-term observations, once they have reached a critical length, need to be used to test the quality of wind-driven simulations. This study presents one step in this direction.

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Storm-driven across-shelf oceanic flows into coastal waters - Sam Jones; Mark Inall; Marie Porter; Jennifer A. Graham; Finlo Cottier (Ocean Science, 2020)
The North Atlantic Ocean and northwest European shelf experience intense low-pressure systems during the winter months. The effect of strong winds on shelf circulation and water properties is poorly understood as observations during these episodes are rare, and key flow pathways have been poorly resolved by models up to now. We compare the behaviour of a cross-shelf current in a quiescent period in late summer, with the same current sampled during a stormy period in midwinter, using drogued drifters. Concurrently, high-resolution time series of current speed and salinity from a coastal mooring are analysed. A Lagrangian analysis of modelled particle tracks is used to supplement the observations. Current speeds at 70 m during the summer transit are 10–20 cm s−1, whereas on-shelf flow reaches 60 cm s−1 during the winter storm. The onset of high across-shelf flow is identified in the coastal mooring time series, both as an increase in coastal current speed and as an abrupt increase in salinity from 34.50 to 34.85, which lags the current by 8 d. We interpret this as the wind-driven advection of outer-shelf (near-oceanic) water towards the coastline, which represents a significant change from the coastal water pathways which typically feed the inner shelf. The modelled particle analysis supports this interpretation: particles which terminate in coastal waters are recruited locally during the late summer, but recruitment switches to the outer shelf during the winter storm. We estimate that during intense storm periods, on-shelf transport may be up to 0.48 Sv, but this is near the upper limit of transport based on the multi-year time series of coastal current and salinity. The likelihood of storms capable of producing these effects is much higher during positive North Atlantic Oscillation (NAO) winters.

Significance of Climate Indices to Benthic Conditions Across the Northern North Atlantic and Adjacent Shelf Seas - Clare Johnson; Mark Inall; Stefan Gary; Stuart Cunningham (Frontiers in Marine Science, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Observing Internal Tides in High-Risk Regions Using Co-located Ocean Gliders and Moored ADCPs - Rob Hall; Barbara Berx; Mark Inall (Oceanography, 2017)

Large-scale forcing of the European Slope Current and associated inflows to the North Sea - Robert Marsh; Ivan D. Haigh; Stuart A. Cunningham; Mark E. Inall; Marie Porter; Ben I. Moat (Ocean Science, 2017)
The European Slope Current provides a shelf-edge conduit for Atlantic Water, a substantial fraction of which is destined for the northern North Sea, with implications for regional hydrography and ecosystems. Drifters drogued at 50 m in the European Slope Current at the Hebridean shelf break follow a wide range of pathways, indicating highly variable Atlantic inflow to the North Sea. Slope Current pathways, timescales and transports over 1988–2007 are further quantified in an eddy-resolving ocean model hindcast. Particle trajectories calculated with model currents indicate that Slope Current water is largely recruited from the eastern subpolar North Atlantic. Observations of absolute dynamic topography and climatological density support theoretical expectations that Slope Current transport is to first order associated with meridional density gradients in the eastern subpolar gyre, which support a geostrophic inflow towards the slope. In the model hindcast, Slope Current transport variability is dominated by abrupt 25–50 % reductions of these density gradients over 1996–1998. Concurrent changes in wind forcing, expressed in terms of density gradients, act in the same sense to reduce Slope Current transport. This indicates that coordinated regional changes of buoyancy and wind forcing acted together to reduce Slope Current transport during the 1990s. Particle trajectories further show that 10–40 % of Slope Current water is destined for the northern North Sea within 6 months of passing to the west of Scotland, with a general decline in this percentage over 1988–2007. Salinities in the Slope Current correspondingly decreased, evidenced in ocean analysis data. Further to the north, in the Atlantic Water conveyed by the Slope Current through the Faroe–Shetland Channel (FSC), salinity is observed to increase over this period while declining in the hindcast. The observed trend may have broadly compensated for a decline in the Atlantic inflow, limiting salinity changes in the northern North Sea during this period. Proxies for both Slope Current transport and Atlantic inflow to the North Sea are sought in sea level height differences across the FSC and between Shetland and the Scottish mainland (Wick). Variability of Slope Current transport on a wide range of timescales, from seasonal to multi-decadal, is implicit in sea level differences between Lerwick (Shetland) and Tórshavn (Faroes), in both tide gauge records from 1957 and a longer model hindcast spanning 1958–2012. Wick–Lerwick sea level differences in tide gauge records from 1965 indicate considerable decadal variability in the Fair Isle Current transport that dominates Atlantic inflow to the northwest North Sea, while sea level differences in the hindcast are dominated by strong seasonal variability. Uncertainties in the Wick tide gauge record limit confidence in this proxy.

The ECO-MAR (Ecosystem of the Mid-Atlantic Ridge at the Sub-Polar Front and Charlie Gibbs Fracture Zone) project: description of the benthic sampling programme 2007–2010 - Imants G. Priede; David S.M. Billett; Andrew S. Brierley; A. Rus Hoelzel; Mark Inall; Peter I. Miller (Marine Biology Research, 2013)

Are Any Coastal Internal Tides Predictable? - Jonathan Nash; Emily Shroyer; Samuel Kelly; Mark Inall; Timothy Duda; Murray Levine; Nicole Jones; Ruth Musgrave (Oceanography, 2012)

Dissipation of Tidal Energy and Associated Mixing in a Wide Fjord - Mark E. Inall; Tom P. Rippeth (Environmental Fluid Mechanics, 2002)